Estudo das propriedades vibracionais do cristal de timidina em condições extremas de pressão e temperatura - Barboza, Felipe Moreira (2017)
The unit of sugar and base connected by a N-β-glycosyl linkage is named a nucleoside. In the present work the nucleoside thymidine, whose molecular formula is C10N2O5H14, was studied by Raman spectroscopy, subjecting it extreme conditions of pressure and temperature, as well as X ray diffraction measurements. An auxiliary analysis of normal crystal vibration modes was performed using first principles calculations using the B3LYP functional together with the Gaussian bases 6-31G+(d) and potential energy distribution analysis (PED). These results, together with literature data and Raman spectroscopy measurements in several thymidine scattering geometries, allowed the identification of the various normal modes of crystal vibration. X-ray diffraction experiments were performed in the temperature range between 83 and 413 K. Experiments of Raman spectroscopy under extreme temperature conditions (20 to 380 K) were performed in the spectral range of 20 to 3400 cm-1. From the analysis of the results, it is possible to draw some conclusions. (i) The thymidine crystal remained stable throughout the investigated temperature range, indicating that the temperature effect is not sufficient to modify the hydrogen bonds present between the molecules in such a way as to modify the symmetry of the crystal. (ii) The material studied showed some slight changes in the vibrational spectra in the experiment performed at low temperatures, suggesting, if not a structural phase transition, at least some conformational modification of the thymidine molecules. Raman spectra of thymidine crystal were obtained for pressures up to 5.0 GPa in a diamond anvil cell. The results show the presence of anomaly in the Raman spectrum at pressures close to 3.0 GPa. This anomaly is characterized by disappearance of lattice modes, appearance of some internal modes, splitting of high wavenumbers modes, downshift of modes associated with hydrogen bonds, changes in the intensity of internal modes and discontinuities of the slopes of the wavenumbers versus pressure for several Raman modes. This set of modifications was interpreted as consequence of a phase transition undergone by thymidine close to 3.0 GPa. Further, decompression to atmospheric pressure generates the original Raman spectrum, showing that the pressure-induced phase transition undergone by thymidine crystals is reversible. A comparison with results on other nucleosides submitted to high pressure is also furnished.